A salicylaldehyde-derived Schiff base composite microwave absorbing material and its preparation method and application

The preparation of salicyaldehyde-derived Schiff alkali metal complex and graphene through microwave radiation method to form a composite absorbing material, which solves the problems of complex preparation and large specific gravity of existing absorbing materials, and achieves strong absorbing performance and small thickness , stable performance effect.

CN117625128BActive Publication Date: 2025-02-11新兴际华(上海)工程科技研究院有限公司
View PDF 4 Cites 0 Cited by

Patent Information

Application Number
CN202311611593.0
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2023-11-29
Publication Date
2025-02-11
Estimated Expiration
2043-11-29

AI Technical Summary

Technical Problem

The existing composite electromagnetic wave absorbing materials are complex in preparation and have a large specific gravity, resulting in increased system weight and limited mobility, and insufficient bonding strength between the coating and the substrate, which is easy to fall off.

Method used

The salicyaldehyde-derived Schiff alkali metal complex is prepared by microwave radiation method, and then it is compounded with graphene by solvothermal method to form a salicyaldehyde-derived Schiff alkali salt/graphene composite absorbing material.

Benefits of technology

It achieves the effects of strong absorbing performance, small thickness, stable performance and simple preparation, solves the problem of large density and large thickness that will increase the weight of the system, and improves the absorption efficiency and stability of the material.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0004576892460000041
    Figure BDA0004576892460000041
  • Figure BDA0004576892460000042
    Figure BDA0004576892460000042
  • Figure BDA0004576892460000043
    Figure BDA0004576892460000043
Patent Text Reader

Abstract

The present invention discloses a salicylaldehyde-derived Schiff base composite absorbing material and a preparation method and application thereof. The composite absorbing material is a product obtained by compounding a salicylaldehyde-derived Schiff base metal complex with graphene by a solvent thermal method. The present invention adopts a microwave radiation method to prepare the salicylaldehyde-derived Schiff base, and the preparation method is simple and easy to operate. Graphene has the advantages of small specific gravity, stable performance, and electrical loss to electromagnetic waves. The composite absorbing material can achieve electromagnetic impedance matching, and obtains excellent absorbing effect through the synergistic effect of the salicylaldehyde-derived Schiff base metal complex and graphene.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of preparation of wave absorbing and electromagnetic protection materials, and specifically relates to a salicylaldehyde-derived Schiff base composite wave absorbing material and a preparation method and application thereof. Background Art

[0002] Absorbing materials refer to a type of material that can absorb electromagnetic waves projected onto its surface and convert electromagnetic wave energy into electrical energy or other forms of energy through the unique properties of the material. There are a large number of outstanding problems that need to be solved in absorbing materials: the narrow absorption bandwidth cannot resist the comprehensive reconnaissance of wide-band radar waves, and the absorption efficiency is low; the high density and thickness of the absorbing material will greatly increase the weight of the system and affect the maneuverability of the system; the bonding strength between the coating and the substrate is insufficient and easy to fall off. At present, absorbing materials are developing in the direction of thin coating thickness, light weight, wide absorption bandwidth, and strong absorption in the low frequency band.

[0003] CN 105001636 B A ferrocene-based chiral poly-Schiff base salt / graphene composite wave absorbing material patent, compared with other composite wave absorbing materials, the prepared composite wave absorbing material has improved wave absorbing performance, wave absorbing bandwidth, density, thickness and performance stability, but still needs to be improved. Moreover, the preparation process uses a traditional synthesis method, the steps are cumbersome, and the use of more organic solvents causes serious environmental pollution. CN 113423256 A belongs to the field of wave absorbing material technology, and provides a composite wave absorbing material and its preparation method and application. The present invention effectively assembles hollow mesoporous carbon spheres with significant dielectric loss and disk-like α-Fe2O3, so that the obtained composite wave absorbing material has both lightweight characteristics and efficient wave absorbing characteristics: in terms of structure, the present invention cleverly conceives and prepares a "football-shaped" nanostructure, which not only effectively solves the problem that disk-like α-Fe2O3 is easy to agglomerate due to its high activity, but also greatly increases the net effective wave absorbing area of ​​the composite wave absorbing material, and improves the wave absorbing performance of the composite wave absorbing material. However, the invention uses mesoporous carbon and iron oxide to assemble, and the composite material has a large mass ratio. Summary of the invention

[0004] The present invention aims at the disadvantages of the existing composite electromagnetic wave absorbing materials, which are complicated to prepare and have a large specific gravity, and provides a composite wave absorbing material of a salicylaldehyde-derived Schiff base substance and a graphene material. The present invention adopts a microwave radiation method to prepare a salicylaldehyde-derived Schiff base metal complex, and then uses a solvent thermal method to composite it with graphene. Through the synergistic composite of multi-component materials, the prepared product of the present invention, the salicylaldehyde-derived Schiff base salt / graphene composite wave absorbing material, has the advantages of strong wave absorbing performance, small thickness, stable performance and simple preparation.

[0005] The salicylaldehyde-derived Schiff base composite absorbing material provided by the present invention is a product obtained by compounding a salicylaldehyde-derived Schiff base metal complex with graphene through a solvent thermal method, wherein the mass ratio of the salicylaldehyde-derived Schiff base metal complex to the graphene can be 2 to 4:1;

[0006] The salicylaldehyde-derived Schiff base metal complex is prepared by a method comprising the following steps:

[0007] 1) salicylaldehyde and aromatic diamine are subjected to microwave-assisted reaction in a microwave high-pressure reactor to obtain a Schiff base ligand;

[0008] 2) The Schiff base ligand and the salt of the central metal ion are subjected to microwave-assisted reaction in a microwave high-pressure reactor to obtain a salicylaldehyde-derived Schiff base metal complex.

[0009] In step 1), the aromatic diamine may specifically be m-phenylenediamine;

[0010] The molar ratio of salicylaldehyde to aromatic diamine may be 2 to 2.2:1, specifically 2.1:1;

[0011] The microwave power of the microwave-assisted reaction is: 200-1000W; the reaction temperature is 60-120°C, and the reaction time is 20-40min, specifically 80°C for 30min;

[0012] In step 2), the central metal ion can be selected from: zinc ion, cobalt ion, iron ion;

[0013] The molar ratio of the Schiff base ligand to the central metal ion may be 0.8 to 1.2:1, specifically 1:1;

[0014] The microwave power of the microwave-assisted reaction is 200-1000W; the reaction temperature is 30-90°C; the reaction time is 10-50min, specifically 60°C for 30min.

[0015] The salicylaldehyde-derived Schiff base composite absorbing material is prepared by a method comprising the following steps:

[0016] A salicylaldehyde-derived Schiff base metal complex is prepared, the salicylaldehyde-derived Schiff base metal complex is ultrasonically dispersed in methanol to obtain a Schiff base metal complex methanol suspension; graphene is ultrasonically dispersed in methanol to obtain a graphene methanol dispersion; the Schiff base metal complex methanol suspension and the graphene methanol dispersion are placed in a reaction kettle, sealed, and reacted; the product is filtered under reduced pressure, dried, and ball-milled in a ball mill to obtain a Schiff base metal complex / graphene composite product, i.e., a salicylaldehyde-derived Schiff base composite wave absorbing material.

[0017] In the above method, the mass ratio of the salicylaldehyde-derived Schiff base metal complex to graphene can be 2-4:1. The reaction temperature can be 30-50°C, and the reaction time can be 40-60 min, specifically 40°C for 50 min.

[0018] Compared with the prior art, the invention has the following beneficial effects:

[0019] Compared with the traditional condensation reflux synthesis method for preparing salicylaldehyde-derived Schiff base metal complexes, the present invention adopts microwave heating, which is simple to operate, has a fast heating rate, can significantly shorten the reaction time, and reduces energy consumption. It solves the problems of large loss of volatile components in the sample preparation process, environmental pollution, and health hazards.

[0020] The present invention uses a salicylaldehyde-derived Schiff base metal complex and graphene in a composite wave absorbing material, and the prepared product has the advantages of strong wave absorbing performance, wide wave absorbing frequency band, low density, thin thickness, simple preparation, etc. The salicylaldehyde-derived Schiff base is prepared by microwave radiation method, and the preparation method is simple and easy to operate. Graphene has the advantages of small specific gravity, stable performance, and electrical loss to electromagnetic waves. The composite wave absorbing material can achieve electromagnetic impedance matching, and obtains excellent wave absorbing effect through the synergistic effect of the salicylaldehyde-derived Schiff base metal complex and graphene.

[0021] The salicylaldehyde-derived Schiff base / graphene composite absorbing material of the present invention can achieve a maximum absorption of -34.15 dB at a thickness of 3.5 mm and a frequency of 13.52 GHz. The absorbing material can achieve a maximum attenuation of -25.30 dB at a thickness of 4.0 mm and a frequency of 2-18 GHz. The salicylaldehyde-derived Schiff base is prepared by a microwave radiation method, and the preparation method is simple and easy to operate. Graphene has the advantage of low density, and the composite absorbing material can solve the problem of high density of ordinary absorbing materials, and an excellent absorbing effect is obtained through the synergistic effect of the salicylaldehyde-derived Schiff base metal complex and graphene.

[0022] In the salicylaldehyde-derived Schiff base metal complex / graphene composite absorbing material of the present invention, the salicylaldehyde-derived Schiff base is a low-density organic material, and graphene also has the advantage of low density. The combination of the two solves the problem of high density of common absorbing materials. The present invention adopts microwave radiation method to prepare the salicylaldehyde-derived Schiff base metal complex, which is convenient to prepare and simple to operate. DETAILED DESCRIPTION

[0023] The present invention is further described in detail below in conjunction with specific embodiments, and the examples provided are only for illustrating the present invention, rather than for limiting the scope of the present invention. The examples provided below can be used as a guide for further improvements by those of ordinary skill in the art, and do not constitute a limitation of the present invention in any way.

[0024] The experimental methods in the following examples, unless otherwise specified, are all conventional methods, and are performed according to the techniques or conditions described in the literature in the field or according to the product instructions. The materials, reagents, etc. used in the following examples, unless otherwise specified, can all be obtained from commercial channels.

[0025] Example 1

[0026] Prepare 0.2 mol / L salicylaldehyde solution and 0.1 mol / L m-phenylenediamine solution, take 10 mL of 0.2 mol / L salicylaldehyde solution and drop it into 10 mL of m-phenylenediamine solution, stir, then transfer the mixed solution into a microwave high-pressure reactor (microwave power 800 W), react at 80°C for 30 minutes, cool, wash three times with anhydrous ethanol, centrifuge, and dry in a vacuum dryer to obtain salicylaldehyde m-phenylenediamine ligand.

[0027] Prepare 0.1 mol / L ZnCl2 solution and 0.1 mol / L salicylaldehyde meta-phenylenediamine ligand solution, take 10 mL of Zn ion solution and slowly drop it into 10 mL of salicylaldehyde meta-phenylenediamine ligand solution, stir, and then transfer the mixed solution into a microwave high-pressure reactor (microwave power 800 W), react at 60°C for 30 minutes, cool, wash three times with anhydrous ethanol, centrifuge, and dry in a vacuum dryer to obtain salicylaldehyde meta-phenylenediamine zinc complex.

[0028] 6 g of the prepared salicylaldehyde metaphenylenediamine zinc complex was placed in 20 mL of methanol for ultrasonic dispersion to obtain a salicylaldehyde metaphenylenediamine zinc complex methanol suspension; 2 g of graphene was placed in 10 mL of methanol for ultrasonic dispersion to obtain a graphene methanol dispersion;

[0029] The prepared salicylaldehyde meta-phenylenediamine zinc complex methanol suspension and graphene methanol dispersion were placed in a polytetrafluoroethylene closed reactor and reacted at 40°C for 40 minutes; the product was filtered under reduced pressure, the filter cake was dried at 45°C for 24 hours, and then ball-milled in a ball mill at a speed of 120r / min for 45 minutes to obtain a composite product of salicylaldehyde meta-phenylenediamine zinc complex / graphene, that is, a salicylaldehyde-derived Schiff base metal complex / graphene composite absorbing material.

[0030] The electromagnetic parameters of the material were tested using a N5234A vector network analyzer with a test frequency range of 1-18 GHz. Its wave absorption performance was estimated according to the following equation:

[0031]

[0032]

[0033] The absorbing material has a thickness of 4.0 mm and can achieve a maximum attenuation of -25.30 dB in the range of 2-18 GHz. The absorption band below -5 dB is 6.5 GHz.

[0034] Example 2

[0035] Prepare 0.2 mol / L salicylaldehyde solution and 0.1 mol / L m-phenylenediamine solution, take 10 mL of 0.2 mol / L salicylaldehyde solution and drop it into 10 mL of m-phenylenediamine solution, stir, then transfer the mixed solution into a microwave high-pressure reactor (microwave power 800 W), react at 80°C for 30 minutes, cool, wash three times with anhydrous ethanol, centrifuge, and dry in a vacuum dryer to obtain salicylaldehyde m-phenylenediamine ligand.

[0036] Prepare 0.1 mol / L CoCl2 solution and 0.1 mol / L salicylaldehyde meta-phenylenediamine ligand solution, take 10 mL of Co ion solution and slowly drip it into 10 mL of salicylaldehyde meta-phenylenediamine ligand solution, stir, and then transfer the mixed solution into a microwave high-pressure reactor (microwave power 800 W), react at 60°C for 30 minutes, cool, wash three times with anhydrous ethanol, centrifuge, and dry in a vacuum dryer to obtain salicylaldehyde meta-phenylenediamine cobalt complex.

[0037] 5 g of the prepared salicylaldehyde metaphenylenediamine cobalt complex was placed in 10 mL of methanol for ultrasonic dispersion to obtain a salicylaldehyde metaphenylenediamine cobalt complex methanol suspension; 2 g of graphene was placed in 10 mL of methanol for ultrasonic dispersion to obtain a graphene methanol dispersion;

[0038] The prepared salicylaldehyde meta-phenylenediamine cobalt complex methanol suspension and graphene methanol dispersion were placed in a polytetrafluoroethylene closed reactor and reacted at 40°C for 40 minutes; the product was filtered under reduced pressure, the filter cake was dried at 45°C for 24 hours, and then ball-milled in a ball mill at a speed of 120r / min for 45 minutes to obtain a composite product of salicylaldehyde meta-phenylenediamine cobalt complex / graphene, that is, a salicylaldehyde-derived Schiff base metal complex / graphene composite absorbing material.

[0039] The electromagnetic parameters of the material were tested using a N5234A vector network analyzer with a test frequency range of 1-18 GHz. Its wave absorption performance was estimated according to the following equation:

[0040]

[0041]

[0042] When the thickness is 3.5mm, the maximum attenuation can reach -34.15dB in the range of 2-18GHz. The absorption band below -5dB is 5.9GHz.

[0043] The present invention has been described in detail above. For those skilled in the art, without departing from the purpose and scope of the present invention, and without the need to carry out unnecessary experimental conditions, the present invention can be implemented in a wide range under equivalent parameters, concentrations and conditions. Although the present invention provides specific embodiments, it should be understood that the present invention can be further improved. In a word, according to the principles of the present invention, the application is intended to include any changes, uses or improvements to the present invention, including departure from the disclosed scope in the application, and changes made with conventional techniques known in the art.

Claims

1. A salicylaldehyde-derived Schiff base composite absorbing material, which is a product of a salicylaldehyde-derived Schiff base metal complex and graphene composited by a solvothermal method, wherein: The mass ratio of the salicylaldehyde-derived Schiff base metal complex to graphene is 2-4:1; The salicylaldehyde-derived Schiff base metal complex is prepared by a method comprising the following steps: 1) Salicylaldehyde and aromatic diamine are subjected to microwave-assisted reaction in a microwave high-pressure reactor to obtain a Schiff base ligand; 2) The Schiff base ligand and the salt of the central metal ion are subjected to microwave-assisted reaction in a microwave high-pressure reactor to obtain a salicylaldehyde-derived Schiff base metal complex; In step 1), the aromatic diamine is m-phenylenediamine; In step 2), the central metal ion is selected from: zinc ion, cobalt ion, and iron ion.

2. The composite absorbing material according to claim 1, characterized in that: In step 1), the molar ratio of salicylaldehyde to aromatic diamine is 2-2.2:1; The microwave power of the microwave-assisted reaction is 200-1000W; the reaction temperature is 60-120°C; and the reaction time is 20-40min.

3. The composite absorbing material according to claim 1, characterized in that: In step 2), the molar ratio of the Schiff base ligand to the central metal ion is 0.8-1.2:1; The microwave power of the microwave-assisted reaction is 200-1000W; the reaction temperature is 30-90°C; and the reaction time is 10-50min.

4. A method for preparing the salicylaldehyde-derived Schiff base composite absorbing material according to claim 1, comprising the following steps: preparing a salicylaldehyde-derived Schiff base metal complex, ultrasonically dispersing the salicylaldehyde-derived Schiff base metal complex in methanol to obtain a Schiff base metal complex methanol suspension; ultrasonically dispersing graphene in methanol to obtain a graphene methanol dispersion; placing the Schiff base metal complex methanol suspension and the graphene methanol dispersion in a reaction kettle, sealing them, and reacting them; the product is filtered under reduced pressure, dried, and ball-milled in a ball mill to obtain a Schiff base metal complex / graphene composite product, i.e., the salicylaldehyde-derived Schiff base composite absorbing material.

5. The method according to claim 4, characterized in that: The mass ratio of the salicylaldehyde-derived Schiff base metal complex to graphene is 2-4:

1.

6. The method according to claim 4, characterized in that: The reaction temperature is 30-50°C and the reaction time is 40-60min.

Citation Information

Patent Citations

  • A ferrocene-based chiral poly-Schiff base salt / graphene composite wave-absorbing material

    CN105001636B

  • Composite wave-absorbing material as well as preparation method and application thereof

    CN113423256A

  • Method for quickly synthesizing Schiff base composition under assistance of microwaves and fluorescence property of Schiff base composition

    CN102391293A

  • Ferrocenyl chiral poly schiff base salt / graphene composite wave absorbing material

    CN105001636A